2023
DOI: 10.1021/acsami.2c16326
|View full text |Cite
|
Sign up to set email alerts
|

Heuristics for Molten-Salt Synthesis of Single-Crystalline Ultrahigh-Nickel Layered Oxide Cathodes

Abstract: In pursuit of Li-ion batteries with higher energy density, ultrahigh-nickel layered oxides are a leading candidate for next-generation cathode materials. Single-crystalline morphology offers a neat solution to the poor stability of ultrahigh-Ni cathodes; a lower active surface area mitigates electrolyte decomposition at high voltages, and the elimination of grain boundaries improves mechanical resilience and increases volumetric energy density. However, single-crystal cathodes possess their own challenges, sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 38 publications
(85 reference statements)
0
33
0
Order By: Relevance
“…Similar to sodium salts, lithium salts have also been widely utilized as flux agents for lowering the melting point of reactants, such as Li 2 MoO 4 , [62] LiCl, [63][64][65] LiNO 3 , [66][67][68] Li 2 O 2 [69] and Li 2 SO 4 . [70][71][72][73] For instance, Li 2 MoO 4 , possessing a melting point of 704 °C, has been utilized as a flux agent in the preparation of SC-NCM111.…”
Section: Molten-salt Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to sodium salts, lithium salts have also been widely utilized as flux agents for lowering the melting point of reactants, such as Li 2 MoO 4 , [62] LiCl, [63][64][65] LiNO 3 , [66][67][68] Li 2 O 2 [69] and Li 2 SO 4 . [70][71][72][73] For instance, Li 2 MoO 4 , possessing a melting point of 704 °C, has been utilized as a flux agent in the preparation of SC-NCM111.…”
Section: Molten-salt Methodsmentioning
confidence: 99%
“…study, in combination with Li 2 O 2 and LiOH, LiNO 3 effectively facilitated the oxidization of Ni, benefiting the formation of a well-structured SC-LNO with suppressed Li/Ni mixing. [69] Li 2 SO 4 possesses a suitable melting point of 859 °C and has been employed as a molten salt for the synthesis of SC-NCM622 [70] andSC-NCM811. [71] A plate-like polyhedral SC-NCM622 with the size of 2 μm was prepared by sintering at 900 °C for 10 h with 9.1mol% Li 2 SO 4 .…”
Section: Molten-salt Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This will likely remain a significant challenge for the foreseeable future, as something simple such as targeting the same particle size with different dopants would require different synthetic conditions to compensate for changes in crystallization kinetics with inclusion of said dopants. In addition, something such as size distribution, which is observed to broaden with greater particle size, [33,40] can lead to aforementioned complications in material performance. In general, there exists three popular methods for SC preparation:…”
Section: Discussionmentioning
confidence: 99%
“…[ 40 ] This is to be expected, as high‐nickel cathodes generally see minimal cation mixing over the course of only a few hundred cycles. [ 27,41 ] While high‐nickel cathodes are known to crack with extended cycling, this phenomenon is also generally observed at greater than 200 cycles. Furthermore, it has recently been shown that high‐stability electrolytes such as LHCE further mitigate cracking and microcracking by suppression of the stress‐corrosion cracking mechanism, and cracking is not expected to meaningfully contribute to capacity fade in this system.…”
Section: Resultsmentioning
confidence: 99%